Force production in the first four steps of sprint running - Salo, A. I. T.; Keranen, T.; Viitasalo, J. T. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this investigation was to understand how the athlete produces acceleration during the first steps of sprint running. One athlete performed four starts from starting blocks over a series of four force plates. Horizontal impulse (which directly relates to the acceleration of the athlete) gradually decreased after leaving the blocks, while this decrease was transferred to a gradual increase in vertical force production to support the small but required vertical movement of CM in order to increase flight time (to gain longer steps). It also seems that the body can compensate for some technical mistakes during the performance, as the results revealed that an extended braking time in one step yielded a reduced braking time in the next step. This implied that the increased time in the contact was used to get other body parts into more favourable positions for the next step.